2000
DOI: 10.1023/a:1008346708604
|View full text |Cite
|
Sign up to set email alerts
|

Weekly docetaxel plus gemcitabine or vinorelbine in refractory advanced breast cancer patients: A parallel dose-finding study

Abstract: SummaryPurpose: The objective of this study was to determine the docetaxel MTD when combined with gemcitabine or vinorelbine in advanced breast cancer patients who had received previous anthracycline-based chemotherapy for advanced disease.Patients and methods: Advanced breast cancer patients aged between 18 and 70 with ECOG PS 0-2 who had not responded to, or had relapsed after, first-line anthracycline-based chemotherapy, were randomized to receive either gemcitabine 1000 mg/m 2 or vinorelbine 25 mg/m 2 in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
1

Year Published

2001
2001
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 9 publications
0
14
1
Order By: Relevance
“…We have previously tested DTX in combination with either gemcitabine or vinorelbine administered on days 1 and 8 every 3 weeks. Both ORR and PFS were substantially worse than those observed in the present study [28]. …”
Section: Discussioncontrasting
confidence: 98%
See 1 more Smart Citation
“…We have previously tested DTX in combination with either gemcitabine or vinorelbine administered on days 1 and 8 every 3 weeks. Both ORR and PFS were substantially worse than those observed in the present study [28]. …”
Section: Discussioncontrasting
confidence: 98%
“…Of note, the chance of response and long-term survival in BC patients refractory to both anthracycline and paclitaxel treatment is very poor [3,26,27,28]. Moreover, it should be taken into account that a relevant number of patients had received even a second-line treatment for the metastatic disease.…”
Section: Discussionmentioning
confidence: 99%
“…Docetaxel and vinorelbine have already been tested in phase I combination clinical trials in ABC [4, 5] and non-small cell lung cancer [6,7,8]. However, these studies used different, although conventional, schedules; three studies administered docetaxel as a single dose every 3 weeks and vinorelbine as several doses [4, 6, 7].…”
Section: Introductionmentioning
confidence: 99%
“…In these phase 1 or 1/2 studies, docetaxel was administered at various doses (from 40 to 100 mg/m 2 ) and schedules (mainly on day 8 only, every 3 weeks) [22, 23, 24, 25]. Only recently, a study examined a schedule in which docetaxel was administered on days 1 and 8, every 21 days [26]. The authors concluded that a docetaxel dose of 40 mg/m 2 using this 3-week schedule is safe when combined with gemcitabine at 1,000 mg/m 2 .…”
Section: Discussionmentioning
confidence: 99%